Programmed Cell Death Protein-1 and Other Inhibitory Receptors Expressed by Regulatory T Cells as a Restraining Factor of Checkpoint Therapy - Batorov, Egor; Ostanin, Aleksandr; Chernykh, Elena (Archive of Oncology, 2025)
SUMMARYThe effectiveness of anti-PD-1/PD-L1 targeted therapies focused on the antitumor immune response restoration in the treatment of melanoma and several other tumors has renewed trust in immunotherapy potential. Despite inspiring enthusiasm that led both to the expansion of indications for anti-PD-1/PD-L1 monoclonal antibodies and to an explosive growth in trials of new immune checkpoint inhibitors, a number of unresolved problems remain: relatively low response rates to existing drugs, development of acquired resistance, tumor progression and immune-mediated adverse events. Both the response to anti-checkpoint therapy and possible adverse reactions are based on quantitative and functional changes in malignant cell clones, tumor microenvironment and immune cells. An indispensable role in these interactions is played by regulatory T cells (Tregs), a heterogeneous population of CD4+ T lymphocytes capable of suppressing the immune response. It is known that, like conventional T cells, Tregs up-regulate several checkpoint receptors, including PD-1, TIM-3, LAG-3. However, the biological relevance of such expression and the consequences of Treg checkpoint blockade are vague, as data from in vitro and clinical observations are contradictory. Here, we reviewed the current understanding of inhibitory checkpoint receptor expression by Treg populations and their relationship with the effects of treatment with checkpoint inhibitors.
Keywords: regulatory T cells; type 1 regulatory T cells; checkpoint inhibitors; PD-1; TIM-3; LAG-3; TIGIT